Reference Agent : Mengoptimalkan Pustakawan Dalam Menghidupkan Kembali Layanan Referensi - Dian Kristyanto (Pustakaloka, 2015)
One of the services developed in library is reference service. This service is a featured product that can give information solution for users. For the vital service, reference librarian is demanded to have an innovation, creation and communication skill, so he can serve to user needs for information. This article dealts with the concept of reference librarian  to  the  development  of  ICT  in  order  to  be  agent  of  reference service being a featured service of library.